Using photo-elicitation to explore perceptions of physical activity among young people with cystic fibrosis - Denise Hill (BMC Pulmonary Medicine, 2019)
Background: Physical activity is recommended in the management of cystic fibrosis (CF). The aim of this study was to explore motives, barriers and enablers to physical activity among this population. Methods: Twelve participants (12–18 years) were recruited via convenience sampling. Photo-elicitation alongside semi-structured interviews were used to explore participants’ views and experiences of physical activity.Results: Our findings revealed motives for physical activity including health, enjoyment and autonomy. Those with families who valued physical activity tended to have positive attitudes towards physical activity, and valued and integrated it into their lives. Moreover, they were likely to be intrinsically motivated to be active. Several factors enable and act as barriers to physical activity. Whilst CF influenced physical activity, the majority of enablers and barriers raised where congruent with the general populations.Conclusion: This study provides support that healthcare providers should encourage both young people with CF and their families to be active, and subsequently informs the development of clinical interventions to support physical activity among young people with CF and their families.